Efficacy, Effectiveness, and Safety of Combination Cream (Clindamycin 3%, Tretinoin 0.05%, and Dexamethasone 0.05%) Over Their Monotherapy (Tretinoin 0.05%) in Acne Vulgaris Patients: Scaled-Up Retrospective Cohort Study - Tan, Sukmawati Tansil; Firmansyah, Yohanes; Hendsun, Hendsun; Chandra, Cindy Christella (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Acne vulgaris is an inflammatory disorder that impacts pilosebaceous glands, affecting many adolescents physically and psychologically. The finest acne cream comprises retinoids, antibiotics, and corticosteroids. Accuracy of acne vulgaris therapy affects the healing and prognosis. To compare the efficacy of a single topical cream containing 0.05% Tretinoin to a combination cream containing Clindamycin 3%, Tretinoin 0.05%, and Dexamethasone 0.05%. This was a retrospective cohort study that included 1027 respondents, observing the result of using 2 types of creams for treating acne: 1) a single tretinoin 0.05% cream and 2) a combination cream therapy (Clindamycin 3%, Tretinoin 0.05%, and Dexamethasone 0.05%). The evaluated parameters were mean reduction in acne lesions quantity as the main objective and other side parameters (Spot, Pore, Wrinkle, UV moisture, UV damage, Roughness, Porphyrin, Pigmentation, and Hydration) as the secondary goals. This study shows that there was a significant difference both in primary and secondary endpoints between single tretinoin 0.05% cream and combination cream therapy (Clindamycin 3%, Tretinoin 0.05%, and Dexamethasone 0.05%) with p-value <0.05 in all parameters. As for adverse events, there was no statistically significant difference locally, and no incidence was found systemically. Combination cream (Clindamycin 3%, Dexamethasone 0.05%, and Tretinoin 0.05%) might provide superior primary and secondary efficacy parameters in acne treatment than single tretinoin cream. Keywords: Acne vulgaris, Safety, Effectiveness, Tretinoin, Clindamycin, Dexamethasone